Effects of a strategic self-talk intervention on attention functions. Issue 5 (3rd September 2022) - Galanis, Evangelos; Hatzigeorgiadis, Antonis; Comoutos, Nikos; Papaioannou, Athanasios; Morres, Ioannis D.; Theodorakis, Yannis
ABSTRACT: In the sport psychology literature, the use of self-talk strategies has proven effective for enhancing task performance, and preliminary evidence suggests that the effectiveness of self-talk can be partly attributed to attentional mechanisms. The purpose of the present investigation was to examine the effects of self-talk strategies on different attention functions, namely, alertness, vigilance, focused, selective, divided, and spatial attention. A between-subjects experimental design was adopted. Six experiments were conducted involving 255 (130 males and 125 females) participants (mean age 21.17 ± 2.31), assigned into experimental and control groups. A five-session protocol was implemented including baseline testing, training intervention, and final assessment. The Test Battery for Perception and Attention Functions from the Vienna Test System was used to assess attention functions. The analysis showed that in all experiments, in 14 out of 17 tests, the experimental groups had faster reaction times than the control groups, and a meta-analytic synthesis of the results showed a large effect size ( d  = 0.75). The findings suggest that self-talk benefit the attention functions and support postulations for an attentional interpretation of the facilitating effects of self-talk strategies on task performance.